Математическое и экспериментальное исследование модели оросительного теплообменника из фторопластовых трубок - Данилов, Юрий Борисович; Коломиец, В. Н.; Харченко, М. А.; Ладченко, С. А. (НТУ "ХПИ", 2008)
Shown in this work is a principle possibility of creating effective spray-type high-power heat exchangers that are made of fluoroplastic tubes and designated for cooling of highly aggressive products in different branches of industry including production of sulphuric acid. Mathematical and experimental models of spray-type heat exchangers are researched, principles of creation of industrial block-modular construction are developed.
Keywords: теплообменная аппаратура; полимерные материалы; фторопласт; оросительные конструкции; оросительные холодильники